Changes in Muscle Protein during Fat Oxidation in Indian Mackerel Rastrelliger kanagurta (Cuvier, 1817) and Threadfin Bream Nemipterus japonicus (Bloch, 1791) under Accelerated Conditions - I.P., Lakshmisha; T.V., Sankar; R., Anandan; V., Geethalakshmi; J., Joseph (Fishery Technology, 2025)
Changes in proteins during exposure conditions which favour deterioration (40 Â± 0.50Â°C) of mackerel (Rastrelliger kanagurta) and threadfin bream (Nemipterus japonicus) were investigated. Samples were drawn at regular intervals for quantifying protein solubility viz., sarcoplasmic proteins (SPP) and myofibrillar proteins (MFP). During the study period, both mackerel and threadfin bream showed a decreasing trend in solubility viz., 91 and 88% respectively whereas SPP did not show much change. Results showed that the change in solubility of MFP, in mackerel was more significant (p<0.05) than in threadfin bream, indicating overall loss of protein solubility with exposure.